A photo-bactericidal thin film composite membrane for forward osmosis1. Issue 13 (7th April 2015) - Li, Jingguo; Yin, Lei; Qiu, Guanglei; Li, Xue; Liu, Qing; Xie, Jianping
<x xml:space="preserve">Abstract</x> This paper reports an effective anti-microbial-fouling membrane that could readily use sunlight to effectively inactivate bacteria on the membrane surface.